THE EFFECTIVENESS OF SOCIAL ASSISTANCE IN THE DEVELOPMENT OF HUMAN RESOURCES IN BINA SIWI 2018-2020 - Herpita Wahyuni; Zuly Qodir (Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims to determine the use of social assistance at the Bina Siwi Orphanage, which focuses on developing human resources. The data analysis used qualitative research methods from the results of the library study and the effects of interviews, and then the data was processed with the help of NVivo 12 Plus software with the Crosstab Query, World Cloud feature so that from the data obtained a score that can be assessed for its effectiveness in the utilization of human resource development. This research focuses on the Bina Siwi Orphanage in utilizing social assistance. The study results can be concluded that social service has been carried out well and has been effective. The development of human resources at the orphanage can meet the needs of daily life, such as three meals a day, school education, skills development, and health insurance. Furthermore, the study results positively impact other institutions in the management of social assistance for the advancement of human resources.